2017
DOI: 10.1038/nplants.2016.208
|View full text |Cite
|
Sign up to set email alerts
|

An NPF transporter exports a central monoterpene indole alkaloid intermediate from the vacuole

Abstract: Plants sequester intermediates of metabolic pathways into different cellular compartments, but the mechanisms by which these molecules are transported remain poorly understood. Monoterpene indole alkaloids, a class of specialized metabolites that include the anti-cancer agent vincristine, anti-malarial quinine and neurotoxin strychnine, are synthesized in several different cellular locations. However, the transporters that control the movement of these biosynthetic intermediates within cellular compartments ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 50 publications
1
90
0
Order By: Relevance
“…Transcriptomic and genomic resources are invaluable for the identification of missing genes encoding key enzymes, transporters, and regulatory proteins in C. roseus (Geu-Flores et al, 2012;Van Moerkercke et al, 2015;Larsen et al, 2017;Paul et al, 2017;Payne et al, 2017;Caputi et al, 2018;Patra et al, 2018;Qu et al, 2019). Coexpression analysis of vindoline biosynthetic pathway genes and GATA TFs identified two putative candidates for further characterization (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic and genomic resources are invaluable for the identification of missing genes encoding key enzymes, transporters, and regulatory proteins in C. roseus (Geu-Flores et al, 2012;Van Moerkercke et al, 2015;Larsen et al, 2017;Paul et al, 2017;Payne et al, 2017;Caputi et al, 2018;Patra et al, 2018;Qu et al, 2019). Coexpression analysis of vindoline biosynthetic pathway genes and GATA TFs identified two putative candidates for further characterization (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that a member of the NPF transporter family was related to strictosidine transport and other members of the NPF family have been implicated in iridoid glucoside transport (Larsen et al, 2017;Payne et al, 2017). It has also been reported that various transporters may be involved in the transport of alkaloids (Carqueijeiro et al, 2013;Shitan et al, 2014).…”
Section: Cell-specific Localisation Of Tias In Leaf Tissuementioning
confidence: 99%
“…A glucosinolate transporter 1 (GTR1) in Arabidopsis was identified as jasmonoyl-isoleucine and gibberellin transporter based on its co-expression with jasmonate biosynthetic genes (Saito et al, 2015). Furthermore, Catharanthus roseus CrNPF2.9 was identified by co-expression analysis of the biosynthetic genes of monoterpene indole alkaloids (Payne et al, 2017), and saffron ( Crocus sativus ) CsABCC4a was revealed as a transporter for crocins by narrowing down the candidate transporter genes that were highly expressed in pistils (Demurtas et al, 2019). These reports prompted us to genetically and biochemically investigate candidate transporter genes for isoflavone and soyasaponin transport further.…”
Section: Resultsmentioning
confidence: 99%